Diagenetic Geochemistry of Iron, Sulfur, and Molybdenum in Sediments of the Middle Okinawa Trough Impacted by Hydrothermal Plumes and/or Cold Seeps. Issue 3 (13th March 2023) - Qin, Shuang‐Shuang; Zhu, Mao‐Xu; Sun, Zhilei; Li, Tie; Zhang, Xilin; Geng, Wei; Cao, Hong; Xu, Cuiling; Zhai, Bin; Chen, Ye
Abstract: Iron (Fe), sulfur (S), and molybdenum (Mo) geochemistry in marine sediments impacted by hydrothermal plumes and/or cold seeps is complex and has not been systematically documented. Here we characterize Fe, S, and Mo diagenesis in sediments between the Minami‐Ensei Knoll hydrothermal field and a cold‐seep site of the middle Okinawa Trough. Results show that distances away from the hydrothermal field and the steep trough slope may significantly affect the transport of hydrothermal Fe. The transformation of hydrothermal reactive Fe to poorly reactive or unreactive Fe‐bearing phyllosilicates decreased the relative fractions of highly reactive Fe (FeHR ) in total Fe (FeHR /FeT ). Despite this, the standing stocks of Fe oxides in the methane‐free sediments have not been dampened, indicating no net impacts of hydrothermal Fe inputs on the size of Fe oxides. In the methane‐free sediments, low ratios of total reduced inorganic sulfide (TRIS) to total organic carbon (TOC) (TRIS/TOC), highly 34 S‐depleted pyrite, and low Mo contents suggest that organoclastic sulfate reduction is at low rates and plays a limited role in carbon cycle. In the cold‐seep sediments, however, intense sulfate reduction coupled to anaerobic methane oxidation significantly elevate TRIS/TOC ratios, Mo enrichment, and isotope compositions of Mo and pyrite‐S. This pathway is expected to be important in carbon cycle in the basin due to the wide occurrence of cold seeps. Our results highlight the important controls of the local extreme depositional/diagenetic conditions on sedimentary S and Mo records, with implications for the reconstruction of paleoredox states of the past earth's surface. Plain Language Summary: Submarine methane‐rich cold seeps and hydrothermal venting exert important influences on the geochemistry of iron, sulfur, and molybdenum. However, the influences of the two extreme environments on the three interlinked elements in seafloor have not been well documented. Here, we used solid‐phase chemistry of four sediment cores located between a hydrothermal field and a cold‐seep site in the middle Okinawa Trough to document the impacts of the two extreme environments on the geochemistry of iron, sulfur, and molybdenum. Results show that hydrothermal Fe signature in the sediments is largely controlled by the distances away from the hydrothermal field and the steep slope of the trough; the hydrothermal Fe inputs have no net impacts on sedimentary iron oxide contents due to simultaneous inactivation of reactive Fe. In the methane‐free sediments, sulfate reduction (SR) is coupled mainly to oxidation of sedimentary organic carbon. In the cold‐seep site, however, SR coupled to anaerobic methane oxidation is the main pathway of carbon cycle, leading to significant enrichments of molybdenum and isotopically heavy pyrite. The differences highlight the important control of local extreme depositional/diagenetic conditions on geochemical records of iron, sulfur, and molybdenum, with implications for the reconstruction of paleoredox states in the past. Key Points: Distances away from the vent, steep basin slope and Fe inactivation control the signature of hydrothermal Fe in the basin sediments Low lability of organics limits sulfate reduction (SR) in CH4 ‐free sediments, while CH4 largely facilitates SR in cold‐seep sediments Local extreme conditions exert key controls on S‐Fe‐Mo diagenesis in the basin